Learning from Latin America’s Informal Sector - Peter M. Ward (Latin American Research Review, 2019)
The essay reviews the following works: Slum Health: From the Cell to the Street. Edited by Jason Corburn and Lee Riley. Oakland: University of California Press, 2016. Pp. xvii, 315. $34.95, paperback. ISBN: 9780520281073.   Cities from Scratch: Poverty and Informality in Urban Latin America. Edited by Brodwyn Fischer, Bryan McCann, and Javier Auyero. Durham, NC: Duke University Press, 2014. Pp. 293. $24.95, paperback. ISBN: 9780822355335.   Owners of the Sidewalk: Security and Survival in the Informal City. By Daniel M. Goldstein. Durham, NC: Duke University Press, 2016. Pp. xiv, 334. $26.95 paperback. ISBN: 9780822360452.   Housing and Belonging in Latin America. Edited by Christien Klaufus and Arij Ouweneel. CEDLA Latin American Studies, 105. New York: Berghahn, 2015. Pp. xiii, 330. $120 hardcover. ISBN: 9781782387404.   For a Proper Home: Housing Rights in the Margins of Urban Chile, 1960–2010. By Edward Murphy. Pittsburgh, PA: University of Pittsburgh Press, 2015. Pp. ix, 343. $32.95 paperback. ISBN: 9780822963110.